A Green Analytical Method using Algorithm (PCCA) for Extracting Components’ Contribution from Severely Overlapped Spectral Signals in Pharmaceutical Mixtures - Obaydo, Reem H.; Sakur, Amir Alhaj (Research Journal of Pharmacy and Technology, 2019)
pure component contribution algorithm (PCCA) is a green analytical method was developed for extracting the contribution of each component from a mixture where the components of this mixture are completely overlapped. It is based on elimination the signal of interfering components using mean centering as a processing tool; finally the pure contribution of each component is extracted form complex signals and that worked as a finger-print resolution for the component. (PCCA) has been successfully applied to UV data of binary mixture of ciprofloxacin (CIP) and metronidazole (MET) and each component of this binary overlapped mixture was able to determine in pure form. The results were compared to reported separation method and no significant difference was found regarding both accuracy and precision. The solvent used in this technique is distilled water so this approach was belonged to green analytical chemistry (GAC) and more preferable than Analytical methods which using harmful organic solvent for environment.